Voltage and Frequency Regulation on Isolated AC Three-phase Microgrids via s-DERs (2019)
This paper addresses the voltage regulation problem on isolated three-phase microgrids via passivity-based control (PBC) with a proportional regulator under the abc reference frame. This reference frame is employed to design the proportional controllers to support voltage and frequency profiles on time-varying loads through a combination of small distributed energy resources and battery energy storage systems. The proposed approach avoids using frequency measurements and reduces the complexity of the control problem. PBC theory exploits natural port-Hamiltonian formulations of the power electronic converters to design controllers, guaranteeing stability for closed-loop operation. Two passivity-based proportional controllers are proposed and compared with conventional proportional actions reported in specialized literature. Simulation results show the effectiveness and robustness of the proposed approach to fulfill the control tasks. © 2019 IEEE.